1987
DOI: 10.1111/j.1365-3024.1987.tb00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylcholine‐bearing antigens in filarial nematode parasites: analysis of somatic extracts, in‐vitro secretions and infection sera from Brugia malayi and B. pahangi

Abstract: A set of cross-reactive antigens is described which are present in somatic extracts and in-vitro secretions of the filarial nematodes Brugia pahangi and B. malayi. A monoclonal antibody reactive with a repeating epitope on these molecules readily detects circulating antigen in the serum of animals infected with lymphatic filariae, using either an immunoradiometric assay or enzyme-linked immunosorbent assay (ELISA). This epitope has the immunological reactivity and chemical characteristics of the phosphorylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…In this regard, one nonprotein epitope that has repeatedly been shown to be immunodominant in filarial infection is phosphorylcholine (33)(34)(35)(36)(37)(38)(39). In preliminary experiments (data not shown), we have found that a mAb of the IgM isotype (PC 140) (40) directed against phosphorylcholine does not facilitate the adherence of activated peritoneal cells to larvae.…”
Section: Discussionmentioning
confidence: 92%
“…In this regard, one nonprotein epitope that has repeatedly been shown to be immunodominant in filarial infection is phosphorylcholine (33)(34)(35)(36)(37)(38)(39). In preliminary experiments (data not shown), we have found that a mAb of the IgM isotype (PC 140) (40) directed against phosphorylcholine does not facilitate the adherence of activated peritoneal cells to larvae.…”
Section: Discussionmentioning
confidence: 92%
“…Many of the immunodominant epitopes of these type 2-inducing antigens have been shown to be glycans displaying very unique structures (10,32,34). We had previously observed that mice immunized with an extract of the human nematode parasite Brugia malayi from which N-linked glycans had been enzymatically removed failed to produce antigen-specific IL-4 (unpublished observation).…”
mentioning
confidence: 99%
“…The possibility that monoclonal antibodies directed against filarial antigen may react with Fasciola antigen was examined by ELISA Two antibodies CA,,, and C$,, both directed against the PC epitope of filarial antigens Phosphocholine is a ubiquitous epitope detected in many parasites including the protozoans (Lal and Ottesen, 1989), cestodes (Fletcher d al., 1980) and nematodes (Lal et al, 1987, Maizels et al, 1987. The present study demonstrates that the trematode F. gtganticxl also bears PC epitopes.…”
Section: M4bs To Fdarial Antigen Cross-react With Fasciola Antigenmentioning
confidence: 57%
“…Development of antigen capture assays for human fhriasis have led to identification of phosphocholine (PC) as an immunodominant epitope on filarial parasite (La1 et aZ;, Maizels et al, 1987 and antibodies directed against the PC can detect filarial antigens in most of the infected individuals. Subsequently, it was shown that PC epitope is not only shared among the helminth parasites, but also was present on some protozoan parasites (La1 and Ottesen, 1989).…”
Section: Introductionmentioning
confidence: 99%